2016
DOI: 10.1016/j.neuron.2016.10.022
|View full text |Cite|
|
Sign up to set email alerts
|

Timing Rules for Synaptic Plasticity Matched to Behavioral Function

Abstract: Summary It is widely assumed that the complexity of neural circuits enables them to implement diverse learning tasks using just a few, generic forms of synaptic plasticity. In contrast, we report that synaptic plasticity can itself be precisely tuned to the requirements of a learning task. We found that the rules for induction of long-term and single-trial plasticity at parallel fiber-to-Purkinje cell synapses vary across cerebellar regions. In the flocculus, associative plasticity in vitro and in vivo is narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 39 publications
5
130
0
Order By: Relevance
“…It should be noted that, although this model has been highly influential in theories of cerebellar-based learning, there remains considerable debate over the functional role of the climbing fiber signals and their interaction with simple spike activity [50, 64, 67]. Furthermore, recent physiological data in mice and rats suggest cerebellar modules vary in the firing rate of simple spike activity and exhibit plasticity tuned to different time intervals between parallel and climbing fiber inputs [20, 21, 68]. These recent findings may represent a first glimpse at how the cerebellum could support diverse functions associated with different constraints, despite its relatively uniform structure.…”
Section: Sensorimotor Coordination Prediction and Error-based Learningmentioning
confidence: 99%
“…It should be noted that, although this model has been highly influential in theories of cerebellar-based learning, there remains considerable debate over the functional role of the climbing fiber signals and their interaction with simple spike activity [50, 64, 67]. Furthermore, recent physiological data in mice and rats suggest cerebellar modules vary in the firing rate of simple spike activity and exhibit plasticity tuned to different time intervals between parallel and climbing fiber inputs [20, 21, 68]. These recent findings may represent a first glimpse at how the cerebellum could support diverse functions associated with different constraints, despite its relatively uniform structure.…”
Section: Sensorimotor Coordination Prediction and Error-based Learningmentioning
confidence: 99%
“…Insights on cellular mechanisms are indispensable for valid models of large-scale networks and pathophysiology, and vice versa. In a cerebellum previously conceptualized as rather uniform, rodent electrophysiology has already unveiled different rules for synaptic plasticity (Wadiche and Jahr, 2005;Zhou et al, 2014;Suvrathan et al, 2016), and recently demonstrated some granule cells encode non-sensorimotor predictions and their unexpected violations (Wagner et al, 2017). These data offered novel perspectives on how the cerebellum may be equipped to contribute to diverse cognitive processes, but assessing higher cognition in animals and particularly rodents with a truly translational potential poses a significant challenge.…”
Section: Integrating Cognitive With Cellular Neurosciencementioning
confidence: 99%
“…There are a number of potential reasons for the lack of consistent findings on the link between LTD and learning, including potential off-target effects of the manipulations used to perturb LTD (see discussion in Schonewille et al, 2011), compensation for LTD deficits by other forms of plasticity [8], and selective contribution of LTD to certain cerebellar leaning tasks and not others [7,40,41,50]. Here, we focus on one specific challenge in connecting in vitro LTD results and in vivo learning results, which was highlighted by two recent studies [51,52], namely the lack of a single, definitive protocol for studying LTD in vitro , and our rudimentary understanding of the sensitivity of LTD to variations in the protocols used to induce LTD.…”
Section: Main Textmentioning
confidence: 99%
“…Suvrathan and colleagues discovered that the requirements for the induction of plasticity at the parallel fiber-to-Purkinje cell synapses can vary across regions of cerebellum, and even between nearby Purkinje cells within a region [52]. More specifically, there is heterogeneity in the optimal parallel fiber – Climbing fiber pairing interval for inducing LTD at parallel fiber synapses onto Purkinje cells in different regions of the cerebellum.…”
Section: Main Textmentioning
confidence: 99%